\(\dfrac{x+\sqrt{5}}{\sqrt{x}+\sqrt{x+\sqrt{5}}}+\dfrac{x-\sqrt{5}}{\sqrt{x}-\sqrt{x-\sqrt{5}}}\)
\(=\dfrac{\left(x+\sqrt{5}\right)\cdot\left(\sqrt{x}-\sqrt{x+\sqrt{5}}\right)}{x-x-\sqrt{5}}+\dfrac{\left(x-\sqrt{5}\right)\left(\sqrt{x}+\sqrt{x-\sqrt{5}}\right)}{x-x+\sqrt{5}}\)
\(=\dfrac{\left(x+\sqrt{5}\right)\left(\sqrt{x}-\sqrt{x+\sqrt{5}}\right)+\left(-x+\sqrt{5}\right)\left(\sqrt{x}+\sqrt{x-\sqrt{5}}\right)}{\sqrt{5}}\)
\(=\dfrac{\left(3+\sqrt{5}\right)\left(\sqrt{3}-\sqrt{3+\sqrt{5}}\right)-\left(3-\sqrt{5}\right)\left(\sqrt{3}+\sqrt{3-\sqrt{5}}\right)}{\sqrt{5}}\)
\(=\dfrac{\left(6+2\sqrt{5}\right)\left(\sqrt{6}-\sqrt{6+2\sqrt{5}}\right)-\left(6-2\sqrt{5}\right)\left(\sqrt{6}+\sqrt{6-2\sqrt{5}}\right)}{\sqrt{5}}\)
\(=\dfrac{\left(6+2\sqrt{5}\right)\left(\sqrt{6}-\sqrt{5}-1\right)-\left(6-2\sqrt{5}\right)\left(\sqrt{6}+\sqrt{5}-1\right)}{\sqrt{5}}\)
\(=\dfrac{-12\sqrt{5}+4\sqrt{30}}{\sqrt{5}}\)
\(=-12+4\sqrt{6}\)